Menstrual disorders in the aspect of stress-related reproductive health disorders of women servicemen in the ATO /JFO zone - Burlaka, Олена; Vahnier, Вікторія (Psychosomatic Medicine and General Practice, 2021)
This text is the thesis of the III scientific-practical conference with international participation "Psychosomatic medicine: science and practice". The following is an analysis of the relationship between the manifestations of menstrual dysfunction and the indicators of the hormonal reproductive profile of servicewomen exposed to stressors of the war zone.